International Cooperative Testing on the Amylose Content of Milled Rice - Juliano, Bienvenido O.; Perez, C.M.; Blakeney, A.B.; Castillo, T.; Kongseree, N.; Laignelet, B.; Lapis, E.T.; Murty, V. V. S.; Paule, C.M.; Webb, B.D. (Wiley, 1981)
An international cooperative test was undertaken to determine the reproducibility of the revised simplified amylose assay in nine laboratories.